Density structure beneath the Rungwe volcanic province and surroundings, East Africa from shear-wave velocity perturbations constrained inversion of gravity data - Njinju, Emmanuel A.; Moorkamp, Max; Stamps, D. Sarah (Frontiers in Earth Science, 2023)
Density perturbations in the subsurface are the main driver of mantle convection and can contribute to lithospheric deformation. However, in many places the density structure in the subsurface is poorly constrained. Most geodynamic models rely on simplified equations of state or use linear seismic velocity perturbations to density conversions. In this study, we investigate the density structure beneath the Rungwe Volcanic Province (RVP), which is the southernmost volcanic center in the Western Branch of the East African Rift (EAR). We use shear-wave velocity perturbations (dlnvs) as a reference model to perform constrained inversions of satellite gravity data centered on the RVP. We use the code jif3D with a dlnvs-density coupling criterion based on mutual information to generate a 3D density model beneath the RVP up to a depth of 660 km. Our results reveal a conspicuous negative density anomaly (∼−200 kg/m3) in the sublithospheric mantle (at depths ranging from ∼100 km to ∼250 km) beneath the central part of the Malawi Rift extending to the west, beneath the Niassa Craton, coincident with locations with positive shear-wave velocity perturbations (+7%). We calculate a 3D model of the velocity-to-density conversion factor (f) and find negative f-values beneath the Niassa Craton which suggests the observed negative density anomaly is mostly due to compositional variations. Apart from the Niassa Craton, there are generally positive f-values in the study area, which suggest dominance of temperature control on the density structure. Although the RVP generally shows negative density anomalies and positive f-values, at shallow depths (<120 km), f≈ 0, which suggests important contributions of both temperature and composition on the density structure possibly due to the presence of plume material. The negative buoyancy of the Niassa Craton contributes to its long stability, while constituting a barrier to the southward flow of plume material, thus restricting the southward continuation of magmatism in the Western Branch of the EAR. The presence of a negative-density anomaly where dlnvs are positive is incompatible with models based on the use of simple dlnvs to density conversion factors. These results have implications on how dlnvs models are converted to density perturbations.